(untitled) (ModaPalavra e-periódico, 2020)
From the experience in the Politecnico di Milano, following Laboratorio di Sintesi Finale course, under the responsibility of Professor Giovanni Conti, it was possible to record the steps that configure a process of fashion design and a certain order for them to occur. During this period, it was possible to observe how often vocabulary and practices of industrial design are used, which are sometimes relaxed according to the specific needs of fashion design. In addition to attending Conti’s classes, an exploratory interview was conducted with the Professor, aiming at collecting more precise primary data that were later treated respecting Oral History methods for the construction of reports such as those of Al berti (2013), Poupart (2008) and Velho (1980). Thus, the problematization produced as a result of this research provided some reflections that expose the importance of the practice of fashion design and its institutionalization for the advancement of the f ield in Brazil.